Liberal-Pragmatist Rationale of the Human Rights Culture - Caviglia Marconi, Alessandro (2012)
The author presents the way in which liberal political culture has emerged from radical evil that led to religious wars duringthe Sixteenth and Seventeenth centuries and has become the framework on which the Culture of Human Rights wasinstalled, and then he presents the liberal - pragmatist rationale of that culture. This rationale is based on Richard Rorty'sproposal, which emphasizes the ethical – political aspect of the Human Rights Culture, supplementing it with the legalcontributions of John Rawls. Finally, the author notes a pending task, to achieve its effect, namely the reorganization of theglobal economic system. This task is inspired by Thomas Pogge's proposal.